Power Quality Issues - Zobaa, Ahmed (IntechOpen, 2013)
Given our increasing dependence on technologies, security of the power supply is of the utmost importance. As such, we require cutting-edge and efficient methods of measuring its efficiency and reliability. This book offers chapters on the compression of power quality data, and methods of recognizing and classifying quality in distribution networks. Other chapters cover using robust symmetrical components' estimation to improve quality in weak grids, monitoring the quality of small-scale renewable energy and the use of active power conditioners to mitigate power-quality problems. Several chapters cover harmonic effects, such as case studies of bank harmonic filters, a parameter-estimation methodology and high-frequency harmonics emissions in smart grids. Finally, one contribution evaluates the distortion and imbalance of emission levels in electric networks.